Successful systemic thrombolytic therapy for massive pulmonary embolism in a patient with breast cancer, brain metastasis, and thrombocytopenia: A case report. Issue 8 (5th June 2018) - Alirezaei, Toktam; Hajimoradi, Behzad; Pishgahi, Mehdi; Nekooghadam, Seyyed Mojtaba; Golmohamadi, Mohamad
Key Clinical Message: A female with massive PTE and absolute contraindication for thrombolytic did not meet guidelines due to unavailability of catheter or surgical embolectomy and giving thrombolytic as a last resort to save a life. In such cases, physicians should consider to act outside of the guidelines to save a life. Abstract : A female with massive PTE and absolute contraindication for thrombolytic did not meet guidelines due to unavailability of catheter or surgical embolectomy and giving thrombolytic as a last resort to save a life. In such cases, physicians should consider to act outside of the guidelines to save a life.